Machine Learning-Based Prediction of Financial Behavior Of Customers - Junková, Veronika; Zimmermann, Pavel, 1980-; Palm, Lukáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis proposes a machine learning-based approach to predict the financial behavior of Siemens' internal customers using contracting and billing data. The developed models forecast actual consumption across diverse services, providing enhanced insights into consumption patterns and financial trends. Leveraging comprehensive datasets—including customer attributes, service specifications, contract details, and historical usage records—the analysis combines Graph Neural Networks and XGBoost to improve forecast accuracy. The anticipated outcome is a practical tool that enhances Siemens’ financial planning, service management, and resource allocation processes.
Vedoucí práce: Pavel Zimmermann
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data a analytika pro business [obor dipl. práce]; diplomové práce; master's theses